Weight‐Related Terms Differentially Affect Self‐Efficacy and Perception of Obesity. Issue 9 (17th September 2018) - Hopkins, Christina M.; Bennett, Gary G.
Abstract: Objective: Little work has explored the effect of weight‐related terms on treatment initiation; only one study has investigated weight‐related terms and the psychological constructs associated with treatment uptake. The present study examines the effects of four common weight‐related terms on treatment initiation and the moderating effect of weight bias internalization. Methods: Adult participants with overweight and obesity ( n = 436) were recruited online and asked to read three vignettes describing clinical encounters; the weight‐related term (i.e., "weight, " "BMI, " "obesity, " or "fat") was varied randomly. Participants then reported self‐efficacy, cognitive and emotional illness beliefs about obesity (i.e., illness perception), and interest in a weight loss program. Results: The term "obesity" resulted in the greatest self‐efficacy and perceived control over obesity. "Fat" resulted in the least illness coherence (i.e., understanding of obesity). Weight bias internalization did not moderate the effect of term on self‐efficacy, nor did it moderate illness perception. No differences in weight loss program enrollment were observed. Conclusions: Use of the term "obesity" may promote patients' perceived control and self‐efficacy. Use of "fat" should be avoided. Results suggest that, despite patient and clinician preference for euphemistic weight terms, use of clinical language such as "obesity" may perform better in provider intervention.